Penerapan Pupuk Organik Cair Urine Kambing Dan Limbah Buah Terhadap Pertumbuhan Tanaman Semangka - Natasya Ramadhana; Elrisa Ramadhani; Maya Sari (Agriculture, 2026)
This study was motivated by the high dependence of farmers on inorganic fertilizers, which may reduce soil fertility, and the underutilization of organic wastes such as goat urine, pineapple peels, and banana peels as liquid organic fertilizer (LOF). The objectives of this study were to analyze the effect of LOF derived from goat urine, pineapple peels, and banana peels on the growth and yield of watermelon (Citrullus lanatus), determine the optimum application rate, and evaluate farmers' acceptance and adoption of the technology. The study was conducted from March to May 2026 in Sei Bamban District, Serdang Bedagai Regency, using a non-factorial Randomized Complete Block Design (RCBD) consisting of five treatments and five replications. The treatments were P0 (control), P1 (50 ml + 20 ml), P2 (100 ml + 35 ml), P3 (150 ml + 50 ml), and P4 (200 ml + 65 ml). Observed variables included vine length, number of leaves, flowering age, fruit weight, fruit length, and fruit diameter at harvest (55 days after planting). Data were analyzed using analysis of variance (ANOVA) followed by Duncan's Multiple Range Test (DMRT) at the 5% significance level, while extension effectiveness was evaluated through pre-test and post-test assessments. The results indicated that the application of liquid organic fertilizer significantly affected all growth and yield parameters of watermelon. Treatment P4 produced the best vegetative growth and yield compared with the other treatments. Extension activities also improved farmers' knowledge, attitudes, and adoption of the technology. Therefore, liquid organic fertilizer derived from goat urine, pineapple peels, and banana peels has the potential to serve as an effective, environmentally friendly, and sustainable alternative fertilizer for watermelon cultivation. Keywords: banana peel, goat urine, liquid organic fertilizer, pineapple peel, watermelon.